EFFECTIVE WAYS OF USING PICTURES IN TEACHING GRAMMAR (Modern education and development, 2025)
The article discusses the benefits of using different pictures in teaching grammar to young learners, emphasizing that visuals make grammar more understandable and engaging. It presents methods like contextual images, sentence completion, comics, role-playing, and error correction to enhance learning. Pictures improve memory, engagement, creativity, and logical thinking, making grammar lessons more effective and enjoyable.